PELATIHAN PEMBUATAN VIDEO AJAR UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DARING - Laily Nurlina; Akhmad Fauzan (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
This community service activity aims to train teachers of SMP Muhammadiyah 2 Karang Lewas Purwokerto, Central Java to develop teaching media (videos) so that they can maximize online learning. Application for editing videos using Kinemaster with a laptop or mobile phone. The choice of Kinemaster because it is light and does not burden the cellphone or laptop, easy to install and easy to use online. The methods used are (1) introduction to Kinemaster, (2) how to download the Kinemaster application, and (3) simulation of using the Kinemaster application to edit videos. The material begins with an explanation of the differences between the Distance Learning RPP and the Covid 19 Emergency Curriculum RPP or one sheet RPP. The introduction of this information is expected to be able to motivate teachers to be more creative in designing online learning.